Post-peak, fluid-mediated modification of granulite facies zircon and monazite in the Trivandrum Block, southern India - Taylor, Richard; Clark, Christopher; Fitzsimons, Ian; Santosh, M.; Hand, M.; Evans, Noreen; McDonald, Bradley (Springer, 2014)
The quarry at Kottavattom in the Trivandrum Block of southern India contains spectacular examples of fluid-assisted alteration of high-grade metamorphic rocks. Garnet-biotite gneiss has undergone a change in mineral assemblage to form submetre scale orthopyroxene-bearing patches, later retrogressed to form an amphibole-bearing lithology. These patches, often referred to as arrested or incipient charnockite, crosscut the original metamorphic foliation and are typically attributed to passage of a low aH2O fluid through the rock. Whilst this conversion is recognised as a late stage process, little detailed chronological work exists to link it temporally to metamorphism in the region. Zircon and monazite analysed from Kottavattom not only record metamorphism in the Trivandrum Block but also show internal, lobate textures crosscutting the original zoning, consistent with fluid-aided coupled dissolution-reprecipitation during formation of the orthopyroxene-bearing patches. High-grade metamorphism at the quarry occurred between the formation of metamorphic monazite at ~585 Ma and the growth of metamorphic zircon at ~523 Ma. The fluid-assisted alteration of the garnet-biotite gneiss is poorly recorded by altered zircon with only minimal resetting of the U–Pb system, whereas monazite has in some cases undergone complete U–Pb resetting and records an age for fluid infiltration at ~495 Ma. The fluid event therefore places the formation of the altered patches at least 25 Myr after the zircon crystallisation in the garnet-biotite gneiss. The most likely fluid composition causing the modification and U–Pb resetting of zircon and monazite is locally derived hypersaline brine.